Synergistic effects of polydopamine-coated reduced graphene oxide on osteogenesis and anti-inflammation in periodontitis - Xiaoge Jiang; Xinyi Chen; Qiming Li; Xinyi Li; Kaiwen Zhang; Jiazhen Jiang; Xinrui Men; Wei-Cho Chiou; Song Chen (Journal of Materials Science: Materials in Medicine)
Abstract Owing to its extremely high prevalence and the distressing consequence of tooth loss, periodontitis has attracted substantial research attention. In light of these conditions, graphene-based biomaterials have emerged as a potentially promising approach for periodontal regeneration. This study focuses on the synthesis of polydopamine-coated reduced graphene oxide (RGO@PDA), designed to harness the anti-inflammatory properties of dopamine and the osteogenic potential of graphene oxide for synergistic periodontitis treatment. RGO@PDA was synthesized through a 12-h magnetic stirring process of graphene oxide and dopamine at room temperature. This water-dispersible and biocompatible compound demonstrated remarkable efficacy in enhancing osteogenic differentiation in rat bone mesenchymal stem cells (rBMSCs), evidenced by increased alkaline phosphatase activity, mineralization, and the upregulation of osteogenic genes and proteins. Furthermore, RGO@PDA showed significant capabilities in scavenging reactive oxygen species (ROS) and reducing proinflammatory factor expression. In vivo experiments revealed that RGO@PDA not only alleviated periodontal inflammation but also promoted alveolar bone repair in periodontitis-afflicted rats. These findings underscore RGO@PDA’s dual anti-inflammatory and osteogenic effects, highlighting its potential as a transformative treatment for periodontitis. Graphical Abstract